Design and manufacture of a bed supported tidal turbine model for blade and shaft load measurement in turbulent flow and waves. (July 2017) - Payne, Grégory S.; Stallard, Tim; Martinez, Rodrigo
Abstract: Laboratory testing of tidal turbine models is an essential tool to investigate hydrodynamic interactions between turbines and the flow. Such tests can be used to calibrate numerical models and to estimate rotor loading and wake development to inform the design of full scale machines and array layout. The details of the design and manufacturing techniques used to develop a highly instrumented turbine model are presented. The model has a 1.2 m diameter, three bladed horizontal axis rotor and is bottom mounted. Particular attention is given to the instrumentation which can measure streamwise root bending moment for each blade and torque and thrust for the overall rotor. The model is mainly designed to investigate blade and shaft loads due to both turbulence and waves. Initial results from tests in a 2 m deep by 4 m wide flume are also presented. Highlights: Design and manufacture of a tidal turbine experimental model are presented in detail. The model is aimed at turbulence and wave load measurements. Each blade root is instrumented to measure streamwise bending moment. The shaft is also instrumented to measure rotor thrust and torque. Successful laboratory testing has been carried out.